Genome-wide characterization of chalcone synthase genes in sweet cherry and functional characterization of CpCHS1 under drought stress - Hou, Qiandong; Li, Shuang; Shang, Chunqiong; Wen, Zhuang; Cai, Xiaowei; Hong, Yi; Qiao, Guang (Frontiers in Plant Science, 2022)
Cherries are one of the important fruits with both horticultural ornamental and economic value. The growth of cherry is greatly affected by biotic stress such as drought, which is one of the important factors hindering its development. Chalcone synthase (CHS, EC 2.3.1.74) is a key rate-limiting enzyme in the biosynthetic pathway of flavonoids, which plays an important role in regulating plant growth, development and abiotic stress tolerance. In the current study, three genes encoding chalcone synthase were found in the sweet cherry (Prunus avium L.) genome. The three genes have fewer introns and have higher homology with CHS in Rosaceae. The conserved catalytic sites may be located at Cys163, Phe214, His302 and Asn335. These genes were differentially expressed during dormant flower bud and fruit development. More flavonoids content was detected in the leaves of Chinese cherry (Cerasus pseudocerasus Lindl.), and the pulp was slightly higher than that in the peel. There was no significant difference in the flavonoid content between the aborted kernel and the normal developing kernel. Overexpression of Chinese cherry CpCHS1 in tobacco can improve the germination rate of tobacco seeds in drought environment, and the fresh weight of plantlets in drought environment is higher than that of wild type, and the drought tolerance of tobacco can be improved by increasing the contents of SOD, POD, CAT and Pro. In conclusion, cherry CHS genes are conserved and functionally diverse, which will help to study the functions of flavonoid synthesis pathways in cherries and Rosaceae plants.